Communicative Functions in Arabic Grammatical Structures In Primary School Textbooks (KSSR) 2017 Malaysia/ الوظائف التواصليّة في الأساليب النحويّة العربيّة من خلال الكتب المدرسيّة الابتدائيّة 2017 بماليزيا - Mat Saaid, Siti Norlailasari; Musling, Mohd Nizwan (Ijaz Arabi Journal of Arabic Learning, 2025)
Communication is the primary function of any language in the world, including Arabic, which is expressed in the form of sentences. Early Arab scholars recognized the importance of the communicative aspect in the structure of Arabic grammar. However, later scholars focus on only one aspect of grammar: inflexion. In contrast, grammar is not limited to the conditions at the ends of words. Therefore, this study aims to analyze the communicative functions through grammatical structures in Arabic language textbooks for primary schools in Malaysia (KSSR) for 2017. This study relies on the descriptive method to achieve its main objectives, utilizing Roman Jakobson's theory of language functions as an analytical framework to uncover the communication process and its functions as realized in the language materials presented in the textbook. The study found that using simple grammatical structures is of utmost importance in enhancing communicative competence among students, which aligns with the curriculum's goal of enabling students to use Arabic communicatively with precision in various situations. The study also shows five communicative functions applied in the Arabic grammatical structures in these books: referential, expressive, conative, phatic, and metalinguistic functions. This study may provide new insights for developers of Arabic curricula, presenting Arabic grammatical sentences from a more comprehensive communicative perspective, theoretically and practically, to improve the quality of Arabic language education in primary schools in particular.